The effect of wreapc (word recognition-action-picture contextualisation) instructional protocol on vocabulary acquisition among ESL Malaysian primary school learners - Zachary Farouk Chai (2022)
Teaching vocabulary is significant to provide learners who learn English as a Second Language (ESL) with sufficient word knowledge to be proficient users of language skills. This research particularly explored the effect of an intervention called WReAPC (Word Recognition-Action-Picture-Contextualisation) Instructional Protocol to improve Malaysian Year 5 primary school learners’ vocabulary acquisition. It is a teaching method that integrates techniques and strategies of teaching vocabulary to ESL learners. Generally, this research aimed to investigate the effects of the intervention (WreAPC Instructional Protocol) and how it helps the learners in vocabulary acquisition. To achieve the objectives of this study, a total of 60 research participants who were at low to intermediate level of proficiency were selected from one primary school in Semporna, Sabah and were divided into experimental and control groups. The intervention module was utilised with the experimental group for eight weeks and the control group was taught using the existing vocabulary teaching method. The quantitative data collection from the pre-test and post-test was conducted and qualitative data collection from the teachers’ observation and semi-structured interview was analysed. A paired-samples t-test was used to measure significant differences among the quantitative data. The research findings revealed that the experimental group performed significantly better than the control group. In contrast, a thematic analysis was used to identify themes from the teachers’ observation and semi-structured interviews. The qualitative data via semistructured interview showed how the intervention had improved the learners’ vocabulary acquisition based on the themes of effectiveness, constructive learning, active participation and practicality. Next, the qualitative data via observation revealed the intervention process that improved vocabulary acquisition based on themes; intervention planning, control, assessment and active learning. Thus, WReAPC successfully improved the Year 5 ESL Learners vocabulary acquisition. This study contributed to the ESL learners’ vocabulary acquisition based on word recognition skills, action, picture and contextualisation elements that imperatively impacted their vocabulary acquisition. It was also recommended to implement WReAPC Instructional Protocol for ESL primary school in teaching vocabulary.